224 Malignancy associated pericardial effusion- do we need to drain them all?. (13th January 2020) - Ho, C; Lee, P H; So, T C; Chiang, M C S; Wong, M H; Fong, Y H; Tsang, C F; Cheng, Y W; Luk, N H; Chui, S F; Chan, K C; Wong, C Y; et al.
Abstract: On Behalf: Cardiac Team, Department of Medicine, Queen Elizabeth Hospital Background: Management of significant pericardial effusion in cancer patients is controversial. These patients have poor prognosis, and avoiding unnecessary intervention is important. Close monitoring of symptoms and echocardiogram is often a reasonable option, but inherits risk of cardiac tamponade. Whether pericardial drainage by means of percutaneous pericardiocentesis or surgical pericardiotomy could prevent future deterioration or affect survival is unknown. Purpose: To evaluate the benefit of elective pericardial drainage in malignancy associated pericardial effusion without echocardiographic or clinical evidence of tamponade effect. Methods: From 1st Jul 2014 to 31st Dec 2017, all patients with new onset malignancy-associated pericardial effusion with size more than 1cm were retrospectively analyzed. Patients with clinical or echocardiographic evidence of cardiac tamponade were excluded. We compared pericardial drainage versus monitoring for short-term (30-day), mid-term (90-day) and long term (1 year) survival without need for drainage. Results: 101 patients were retrospectively analyzed. 40 (39.6%) patients underwent drainage. Overall median survival free from drainage was 4 months. There were no significant difference in short-term (30-day), mid-term (90-day) and long term (1-year) survival free from drainage or mortality between treatment and monitoring group. Size of pericardial effusion did not predict mortality or future need of drainage. Chemotherapy was associated with improved 30-day mortality (RR 0.53 CI 0.32-0.87 p = 0.025) but not survival free from drainage or longer term mortality. Conclusion: Close monitoring could be a feasible strategy in cancer patients with significant pericardial effusion without tamponade effect.